A Misconception Investigation of Ninth Grade Students about Magnetism: Investigasi Miskonsepsi Siswa Kelas IX Tentang Materi Kemagnetan - Shofiyah, Noly (Universitas Muhammadiyah Sidoarjo, 2021)
This study aimed to identify the ninth grade students' misconceptions related to magnetism topic. For this purpose, an instrument consisting of two phases (two-tier) with fourteen multiple choice items on magnetism concepts was developed by the researcher. The diagnostic test was given to thirty-two ninth grade students. The findings indicated that 9th grade students experience misconceptions about the concept of magnetism including how to make and determine artificial magnetic poles, Lorentz force and GGL Induction. The results of this study can be used by teachers and researchers to choose substantial learning strategies for teaching magnetism material.